Whole Exome Sequencing allows the identification of two novel groups of Xeroderma pigmentosum in Tunisia, XP-D and XP-E: Impact on molecular diagnosis. Issue 2 (February 2018) - Ben Rekaya, Mariem; Naouali, Chokri; Messaoud, Olfa; Jones, Meriem; Bouyacoub, Yosra; Nagara, Majdi; Pippucci, Tommaso; Jmel, Haifa; Chargui, Mariem; Jerbi, Manel; Alibi, Mohamed; Dallali, Hamza; et al.
Highlights: We identify two very rare and under-diagnosed groups of XP, the XP-E and XP-D. These two groups have never been reported in North Africa region. WES and ROH analysis are effective tools to identify the molecular etiology of autosomal recessive disorders in consanguineous families. In Tunisia, molecular diagnosis of XP should be established to introduce early photo-protection and provide genetic counseling for families at risk. Abstract: Background: Skin cancers (SC) are complex diseases that develop from complex combinations of genetic and environmental risk factors. One of the most severe and rare genetic diseases predisposing to SC is the Xeroderma pigmentosum (XP) syndrome. Objectives: First, to identify the genetic etiology of XP and to better classify affected patients. Second, to provide early molecular diagnosis for pre-symptomatic patient and finally to offer genetic counseling for related individuals. Methods: Whole Exome Sequencing (WES) and Run Of Homozygosity (ROH) were performed for two patients belonging to two different multiplex consanguineous families. The identified mutations were confirmed by Sanger sequencing and researched in ten Tunisian families including a total of 25 affected individuals previously suspected as having XP group V (XP-V) form. All patients had mild dermatological manifestations, absence of neurological abnormalities and late onset of skin tumors. Results: Screening for functional variations showed the presence of the ERCC2 p.Arg683Gln in XP14KA-2 patient and a novel mutation, DDB2 p. (Lys381Argfs*2), in XP51-MAH-1 patient. Sanger sequencing and familial segregation showed that the ERCC2 mutation is present at a homozygous state in 10 affected patients belonging to 3 families. The second mutation in DDB2, is present at a homozygous state in 5 affected cases belonging to the same family. These two mutations are absent in the remaining 10 affected patients. The ERCC2 c.2048G > A mutation is present in a medium ROH region (class B) suggesting that it mostly arises from ancient relatedness within individuals. However, the c.1138delG DDB2 mutation is present in a large ROH region (class C) suggesting that it arises from recent relatedness. Conclusion: To our knowledge, this is the first study that identifies XP-D and XP-E complementation groups in Tunisia. These two groups are very rare and under-diagnosed in the world and were not reported in North Africa.